Holoptelea integrifolia Planch: A potential Ayurvedic medicinal plant - Srivastava J.; Prasad S.K.; Dwivedi K.N.; Pandey H.P. (My University, 2025)
Holoptelia integrifolia Planch (Ulmaceae) is an evergreen, scattered, glabrous tree with 30-35 m in height and is commonly known as Chilbil in India. In India, stem bark and leaves of the plant are used in indigenous system of medicines such as Ayurveda, Unani, Siddha for the prevention of variety of diseases such as bitter, astringent, acrid, anti-inflammatory, digestive, carminative, laxative depurative, and diuretic. Literature survey of plant H. integrifolia showed the presence of various phyto constituents having pharmacological activities such as antioxidant, adaptogen, hepatoprotective, antiulcer, antibacterial, anti-inflammatory and antitumor activity. Thus, the present review will provide up to date referential information to the researchers working on this particular plant.